Adiwiyata Implementation In Understanding Environmental Education - Nur Aeni; Nursalam Nursalam; Idawati Idawati (Indonesian Journal of Primary Education, 2020)
Environmental education is one of the important factors in the success of environmental management and is also a very important means of producing human resources who can implement the principles of improving the quality of education in schools. The purpose of this research is to find out about the efforts in realizing environmental education and the factors that influence the emergence of the Adiwiyata program at SD Negeri Barrang Lompo. This research uses descriptive qualitative. Data were collected through interviews, observation and documentation. This study uses data analysis techniques, which consist of the stages of data collection, data reduction, data presentation and drawing conclusions. The results of research on the implementation of Adiwiyata in an effort to realize environmental education are the first steps, namely creating a team at school and compiling programs to achieve the title of Adiwiyata school, after compiling a team of principals and teachers to implement the program by involving collaboration with the local government, all residents. schools, students and the surrounding community. Teachers and students work together to achieve the Adiwiyata school. The factors that influence the emergence of Adiwiyata schools are the existence of environmental education which can help improve the quality of education. The curriculum used is integrated with environmental learning which greatly assists students in experiencing environmental theory so that they can maintain cleanliness in general according to the importance of environmental cleanliness. after compiling a team of principals and teachers to implement the program by involving collaboration with the local government, all residents. schools, students and the surrounding community. Teachers and students work together to achieve the Adiwiyata school. The factors that influence the emergence of Adiwiyata schools are the existence of environmental education which can help improve the quality of education. The curriculum used is integrated with environmental learning which greatly assists students in experiencing environmental theory so that they can maintain cleanliness in general according to the importance of environmental cleanliness. after compiling a team of principals and teachers to implement the program by involving collaboration with the local government, all residents. schools, students and the surrounding community. Teachers and students work together to achieve the Adiwiyata school. The factors that influence the emergence of Adiwiyata schools are the existence of environmental education which can help improve the quality of education. The curriculum used is integrated with environmental learning which greatly assists students in experiencing environmental theory so that they can maintain cleanliness in general according to the importance of environmental cleanliness. Teachers and students work together to achieve the Adiwiyata school. The factors that influence the emergence of Adiwiyata schools are the existence of environmental education which can help improve the quality of education. The curriculum used is integrated with environmental learning which greatly assists students in experiencing environmental theory so that they can maintain cleanliness in general according to the importance of environmental cleanliness. Teachers and students work together to achieve the Adiwiyata school. The factors that influence the emergence of Adiwiyata schools are the existence of environmental education which can help improve the quality of education. The curriculum used is integrated with environmental learning which greatly assists students in experiencing environmental theory so that they can maintain cleanliness in general according to the importance of environmental cleanliness.